2014
DOI: 10.1007/s00198-014-2882-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses reveal the essential role of SOX6 and RUNX2 in the communication of chondrocyte and osteoblast

Abstract: Our study first reveals that SOX6 and RUNX2 play important roles in the chondrogenesis-osteogenesis coordination. This finding enriches the limited understanding about this coordination and unravels the novel function of SOX6 and RUNX2 in the endochondral ossification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…GDF5 , also called bone morphogenetic protein (BMP)-14 and cartilage-derived morphogenetic protein (CDMP)-1, is a member of the transforming growth factor β (TGF-β) superfamily and plays critical roles in organ development processes including bone, cartilage, ligament, and joint formation [45]. SOX6 , a member of the D subfamily of sex determining region y-box (SRY-box)-related transcription factors, is a crucial transcription factor that regulates chondrogenesis and endochondral ossification [46]. A previous study showed that rhGDF-5 induces the osteogenic differentiation of LF cells through the activation of ERK1/2 and p38 mitogen-activated protein kinase (MAPK) [40].…”
Section: Discussionmentioning
confidence: 99%
“…GDF5 , also called bone morphogenetic protein (BMP)-14 and cartilage-derived morphogenetic protein (CDMP)-1, is a member of the transforming growth factor β (TGF-β) superfamily and plays critical roles in organ development processes including bone, cartilage, ligament, and joint formation [45]. SOX6 , a member of the D subfamily of sex determining region y-box (SRY-box)-related transcription factors, is a crucial transcription factor that regulates chondrogenesis and endochondral ossification [46]. A previous study showed that rhGDF-5 induces the osteogenic differentiation of LF cells through the activation of ERK1/2 and p38 mitogen-activated protein kinase (MAPK) [40].…”
Section: Discussionmentioning
confidence: 99%
“…25 The CpG correlating to the highest number of transcripts (5% FDR) lies within an enhancer in the 3 0 end of SOX6, which is well known to have a significant function in cartilage and bone. 26 Ubiquitin Specific Peptidase 2 (USP2) (6 th and 7 th from top) is induced by the osteotropic agents PTH, PTHrP, and PGE2, 27 but its specific function in bone is not yet known.…”
Section: Methylation At Selected Cpgs Correlates Significantly To a Hmentioning
confidence: 99%
“…SOX6 is a member of the SOX family of transcription factors that is expressed in the cartilage and has an essential role in chondrocyte differentiation, cartilage formation and endochondral bone formation 38 . In fact, a recent functional study revealed that SOX6 is involved in the coordination of chondrogenesis and osteogenesis 39 . The relationship between rs7117858 SNP in SOX6 and certain osteoporosis phenotypes has been previously investigated in mixed populations [23][24][25][26]32 .…”
Section: Resultsmentioning
confidence: 99%